Ex Asia et Syria : Oriental religions in the Roman Central Balkans - Gavrilović, Nadežda, (Archaeopress Roman archaeology ;, 2021)
This title examines the cults of Asia Minor and Syrian origin in the Roman provinces of the Central Balkans. The author analyses all hitherto known epigraphical and archaeological material attesting to the presence of the cults in that region, a subject yet to be the object of serious scholarly study.